Slow ventricular tachycardia induced by amiodarone overdose - Zachary Boivin; Nicholas Pugliese; Peter Quinby (JEM Reports)
Background: Slow ventricular tachycardia (VT) can be difficult to diagnose on electrocardiogram given its atypical rate of less than 120 beats per minute. In patients with implanted defibrillators, slow VT can be overlooked and have detrimental consequences for patients given their decreased cardiac output. In this case, slow VT was identified early, and was caused by an overdose of amiodarone. Case report: A 50-year-old male with an extensive past medical history of polysubstance abuse and heart failure with implanted defibrillator (AICD) presented with a suspected heroin overdose, along with cocaine use, and acute overdose of 20–25 200 mg amiodarone tablets over 48 hours. The patient was found to be in a slow, wide-complex rhythm, and after hyperkalemia was ruled out, electrophysiology was contacted, and they diagnosed the patient with slow VT. This was corrected with overdriving pacing, and the patient was discharge home after a brief admission. Why should an emergency physician be aware of this: There are currently no case reports showing an isolated amiodarone overdose causing slow VT, and while cocaine can cause VT due to its sodium channel blocking effects, the slow rate suggests the amiodarone overdose influenced the cardiac myocytes. This patient was predisposed to developing episodes of VT due to his underlying cardiac conditions and substance use, but had no evidence of slow VT prior to his acute amiodarone overdose. We recommend all providers be aware of the potential arrhythmic complications of isolated amiodarone overdoses, and specifically the management of slow VT, with overdrive pacing as opposed to cardioversion potentially having more success.